Management of neonatal testicular torsion: Which way to turn? - Guerra, Luis A.; Wiesenthal, Joshua; Pike, John; Leonard, Michael P. (Canadian Urological Association Journal, 2013)
Objective: Perinatal testicular torsion (PTT) is a rare event with controversies surrounding its etiology, presentation, surgical management and sequelae. Our survey assessed the preferences of pediatric urologists with regard to its management. Methods: Four cases of unilateral PTT and a questionnaire containing 11 questions about management of common clinical scenarios were mailed to 26 pediatric urologists. The answers were received anonymously and they were analyzed blindly. Results: The response rate was 80% (21/26), with 90% (19/21) of respondents holding academic appointments. In the 2 first cases of PTT with a typical unilateral nonviable testis, 76% (16/21) and 67% (14/21), respectively, opted for surgery. A case of acute postnatal torsion resulted in 100% agreement to urgent scrotal exploration. In the case of an atrophic testis, none of the respondents opted for immediate surgery; yet, 38% (8/21) said they would proceed with a delayed orchiopexy of the contralateral testicle. In the question section, 10% (2/21) responded that they preferred to explore PTT immediately; whereas, 57% (12/21) would delay surgical exploration for a few days until the neonate was better stabilized. One-third of participants (7/21) would not perform a surgical exploration but would just follow the child clinically. A scrotal incision for contralateral orchiopexy was preferred by 52% (11/21), while 48% (10/21) prefer a scrotal approach but would switch to an inguinal incision if a hydrocele were present. Operative intervention was favoured by 80% (8/10) and 46% (5/11) of those with less than and greater than 10 years of practice, respectively. Conclusion: This survey revealed that 67% (14/21) of respondents preferred immediate exploration of a torted testis and contralateral orchiopexy, compared with the nonoperative approach. Scrotal incision for the exploration was preferred by most respondents. There was a trend to choose less aggressive treatment as the years of practice increase. Studies of more robust design, such as randomized controlled trials, are necessary to determine the natural history and outcomes of this uncommon type of testicular torsion.